UJI EFEKTIVITAS PUPUK ORGANIK CAIR DARI URIN TERNAK SAPI DAN KUDA TERHADAP PERTUMBUHAN VEGETATIF TANAMAN SAWI (Brassica juncea L.) - Herlinawati Herlinawati; Iwan Doddy Dharmawibawa; Sucika Armiani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2019)
Mustard Vegetable is an economically valuable vegetable crop, so that community demand for vegetables is increasing. In an effort to meet market needs, mustard production needs to be increased, one of which is by improving the quality of planting media through fertilization. The use of liquid organic fertilizer is faster absorption by plants than solid organic fertilizer. One of the basic ingredients of liquid fertilizer can be using the urine of cattle and horses. This type of research is a pure experiment using a completely randomized design (CRD). The study used 4 treatments 3 replications using liquid organic fertilizer from cow urine and 4 treatments 3 replications using liquid organic fertilizer from horse urine with fertilizer concentrations of 25%, 50% and 100%, with research parameters namely plant height, number of leaves, length leaf, leaf width and wet weight. The technique of data collection is done by observation. The data in this study were analyzed using ANOVA (Analysis of Variance) One Way using SPSS 14 for Windows. The results of research on liquid fertilizer from the urine of cattle and horses significantly affect the rate of growth of mustard plants. The mustard plant has a faster growth rate using liquid fertilizer from cow urine compared to horse urine.